2018
DOI: 10.1016/j.apgeochem.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater chemistry and the Gibbs Diagram

Abstract: The 'Gibbs Diagram' represents some of the key processes controlling surface water chemistry. This review highlights that the processes listed on the Gibbs Diagram may not be applicable for assessing processes controlling groundwater chemistry. We discuss the importance of geochemical processes governing groundwater chemistry in the Gibbs Diagram framework. We show that the processes represented on the Gibbs Diagram-originally developed for surface waters-unlikely represent key processes controlling the chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(100 citation statements)
references
References 30 publications
(41 reference statements)
3
72
0
8
Order By: Relevance
“…The basis of dissolved ionic substances and the processes for the evolution of groundwater are revealed by the graphical procedure as an interface of TDS versus Cl/(Cl + HCO 3 ) and Na/(Na + Ca) ratios [21,61,62]. Precipitation is the preliminary process since the chemical compositions of aquifers are affected by the volume of suspended salts/ions generated by precipitation [21,[61][62][63][64]. Naturally, the volume of precipitation is consistently high surpassing the low quantity of dissolved elements resulting from the rock mineral.…”
Section: Groundwater Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of dissolved ionic substances and the processes for the evolution of groundwater are revealed by the graphical procedure as an interface of TDS versus Cl/(Cl + HCO 3 ) and Na/(Na + Ca) ratios [21,61,62]. Precipitation is the preliminary process since the chemical compositions of aquifers are affected by the volume of suspended salts/ions generated by precipitation [21,[61][62][63][64]. Naturally, the volume of precipitation is consistently high surpassing the low quantity of dissolved elements resulting from the rock mineral.…”
Section: Groundwater Evolutionmentioning
confidence: 99%
“…It helps explains visibly, the pattern of groundwater sources producing a rebound-shaped cloud on a graph. Groundwater is not in a state of equilibrium with aquifer rock mineral, consequent of their mingling with recharged waters with distinct transport periods and often having higher Ca and HCO 3 concentrations when compared with Cl and Na [64]. The hydrochemistry of aquifers in the study area is controlled by rock weathering, as depicted in Fig.…”
Section: Gibbs Diagrammentioning
confidence: 99%
“…All the groundwater samples fell into both the evaporation and rock weathering dominant area, indicating the predominant role of evaporation and rock weathering on groundwater chemistry in the study area. Most shallow groundwater samples were positioned in the evaporation dominant zone, suggesting the significant effect of evaporation and/or dissolution of evaporates [42,43] on shallow groundwater hydrogeochemistry.…”
Section: Mechanisms Of Natural Processes Controlling Groundwater Chemmentioning
confidence: 99%
“…All the groundwater samples fell into both the evaporation and rock weathering dominant area, indicating the predominant role of evaporation and rock weathering on groundwater chemistry in the study area. Most shallow groundwater samples were positioned in the evaporation dominant zone, suggesting the significant effect of evaporation and/or dissolution of evaporates [42,43] on shallow groundwater hydrogeochemistry. The observed good, positive correlation between Na + and SO 4 2− (r = 0.87), Cl − (r = 0.74) (Table S3) and the high concentrations of these major ions in shallow groundwater indicated that evaporates (i.e., halite and mirabilite [44]) dissolution was the major process controlling the shallow groundwater chemistry.…”
Section: Mechanisms Of Natural Processes Controlling Groundwater Chemmentioning
confidence: 99%
“…Geochemical modeling: Geochemical models were used to estimate the chemical reactions in the groundwater system such as dissolution and precipitation of solids, ion-exchange and sorption by clay minerals (Talebi, 2003;Marandi and Shand, 2018). Based on Plummer (1994), the geochemical models can be divided into two general 706 types.…”
Section: Expanded Durov Diagrammentioning
confidence: 99%